The earliest Waqf in Malaysia - Md Dahlan, Salehudin; Yunus, Zulkifli Yunos; Mohamad, Nor Asiah (2018)
The aim of this paper is to report the earliest waqf in Malaysia based on recent findings. Research methodology used is historical research method. It nvolved library research such as books, journal articles, ,conference papers,monograph and theses.The findings are strengthened within interviews with historian,archaeologist and geologist. The research involves several key words including waqf history andMalaysia chapter .The research is important as there is inadequate research on theearliest waqfs in Malaysia as mentioned by previous researchers and wide gap of years between the coming of Islam to Malay Archipelago in 674A.D .and earliest existing mosque in Malaysia dated 1676A.D .It was found out that Islam has reached to Malaysia through Kedah as early n 9th century A.D.